Do Sustainability Rating Schemes Capture Climate Goals?. Issue 1 (January 2021) - Rekker, Saphira A. C.; Humphrey, Jacquelyn E.; O'Brien, Katherine R.
The 2015 Paris Agreement set a global warming limit of 2°C above preindustrial levels. Corporations play an important role in achieving this objective, and methods have recently been developed to map global climate targets to specific industries, and individual corporations within those industries. In this article, we assess whether Sustainability ratings capture corporate performance in meeting the 2°C target. We analyze nine rating schemes used by investors and three commonly used in academic studies. Most rating schemes do consider corporate greenhouse gas emissions in their analysis, whereas only a minority scale emissions by factors that have the potential to allow benchmarking against science-based targets. None take the final step of mapping climate indicators against the 2°C target. Furthermore, we find a lack of consistency in the climate change ratings of the databases used in academic studies. These results are concerning in the context of being able to meet global climate change goals.